2021
DOI: 10.1097/ajp.0000000000001009
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Multidisciplinary Interventions for Chronic Low Back Pain

Abstract: Objective: Chronic musculoskeletal pain in adults is a global health and economic problem. The aim of this paper was to systematically review and determine what proportion of multidisciplinary approaches to managing chronic musculoskeletal pain are cost-effective. Materials and Methods: The EconLit, Embase, and PubMed electronic databases were searched for randomized and nonrandomized economic evaluation studies of nonpharmaceutical multidisciplinary chronic pain management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Despite the evidence that adequate pain management can save costs in an inpatient setting, 2,5 these data show that all government hospitals in Thailand who are refunded based on the ICD-10 coding system cannot receive any reimbursement for managing pain conditions. We propose that this is the case in many hospitals worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the evidence that adequate pain management can save costs in an inpatient setting, 2,5 these data show that all government hospitals in Thailand who are refunded based on the ICD-10 coding system cannot receive any reimbursement for managing pain conditions. We propose that this is the case in many hospitals worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Labor force participation is an important indicator beyond improved health outcomes of tax paid after RTW, less dependence on welfare payments, and less dependence on family members for financial support. 12 Our study also has a number of limitations. First, although our analyses controlled for important known baseline differences for ADAPT patients, other unknown or unmeasured confounders could have contributed to our findings.…”
Section: Strengths and Limitationsmentioning
confidence: 91%
“…Many patients gradually resume activities of normal life, despite persisting pain, after participating in such intensive pain management programs. 22,23,35 A systematic literature review of the cost-effectiveness of multidisciplinary pain management programs 12 suggested that although relatively few studies have examined this issue, some have reported favourable cost-effectiveness outcomes. 28,29 The reviewed studies encouraged additional rigorous economic analysis of such interdisciplinary pain management programs.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-disciplinary care is now considered the gold standard in the care of complex diseases, particularly in our current era of personalized medicine. The value and cost-effectiveness of multidisciplinary care spans numerous disorders, ranging from chronic kidney disease ( 42 ) to congestive heart failure ( 43 ) to amyotrophic lateral sclerosis ( 44 ). For example, multidisciplinary care improves mortality in ALS patients ( 45 ).…”
Section: Multidisciplinary Amyloid Carementioning
confidence: 99%